A copper-oxidized copper composite material and its application in catalyzing ammonia production from nitrate

CN118356936BActive Publication Date: 2026-11-03CHINA PHARM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410047410.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-12
Publication Date
2026-11-03
Estimated Expiration
2044-01-12

AI Technical Summary

Technical Problem

In existing technologies, the accumulation of NO2- in the nitrate reduction reaction by copper electrodes is highly toxic, and the synergistic effect of oxidized copper in the NO3RR process is not well studied, resulting in low efficiency of electrocatalytic reduction of nitrate, and traditional methods are energy-intensive and have poor selectivity.

Method used

A three-step method was used to prepare three-dimensional polycrystalline spherical nanoclusters of copper-oxidized copper composite material, which was loaded onto carbon fiber paper and subjected to wet chemical oxidation, pyrolysis reduction and cyclic voltammetry electrolysis to form a self-supporting stable structure, thereby enhancing the stability of the catalyst and the reaction contact area.

Benefits of technology

It achieved a high Faraday efficiency of up to 98% and a high ammonia yield of 22 mg cm⁻²h⁻¹, significantly improving the electrocatalytic performance of nitrate reduction to ammonia, reducing energy consumption, and making it suitable for practical water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118356936B_ABST
    Figure CN118356936B_ABST
Patent Text Reader

Abstract

The application discloses a copper-oxidized copper composite material and application thereof in catalytic production of ammonia from nitrate, wherein the composite material is loaded on carbon fiber paper and is in a three-dimensional polycrystal spherical nanocluster shape; and the carbon fiber paper loaded with the material is used for electrocatalytic reduction of nitrate, so that nitrate pollution in water bodies can be removed, excellent ammonia production performance, selectivity and anti-interference ability of impurities in actual water bodies can be achieved, and the carbon fiber paper can be used for removing nitrate in actual water bodies and efficiently synthesizing ammonia.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials chemistry, specifically relating to the preparation of a three-dimensional polycrystalline spherical nanocluster copper-oxidized copper composite material and its application in the electrocatalytic reduction of nitrate pollution in water to produce ammonia. Background Technology

[0002] In recent years, ammonia has been widely used in chemical feedstocks and energy transportation due to its energy storage capacity and easy liquefaction. However, traditional ammonia synthesis processes suffer from numerous problems, including harsh operating conditions, over-reliance on fossil fuels, high energy consumption, and high emissions. Therefore, the electrocatalytic reduction of nitrogen to ammonia has attracted considerable attention due to its mild reaction conditions, simple reaction apparatus, and readily available reactants. Although electrocatalytic ammonia synthesis currently faces challenges in selectivity and yield, it offers insights into the conversion of other nitrogen-containing small molecules into ammonia. Therefore, developing an efficient, convenient, and scalable alternative ammonia production process remains a significant challenge and an ideal direction.

[0003] Meanwhile, nitrate pollution from fertilizers and industrial wastewater poses a serious threat to the environment and human health. Traditional nitrate treatment methods include physical, chemical, and biological methods, but these methods suffer from high wastewater discharge and energy consumption. Therefore, developing a low-energy, high-efficiency, and easy-to-implement nitrate removal method is urgent. Electrocatalytic reduction of nitrate to nitrogen has become an important strategy for solving this problem. Furthermore, considering that atmospheric nitrogen still needs to be converted to ammonia via the Haber-Bosch process, methods for directly converting nitrate to ammonia are receiving increasing attention. Electrocatalytic reduction of nitrate to ammonia not only allows for the on-site production of ammonium nitrate fertilizer but also provides an important alternative for efficient ammonia synthesis. Direct conversion of nitrate to ammonia avoids the formation and cracking of inert nitrogen-nitrogen triple bonds, making it a simple, low-energy, and efficient strategy for improving the global nitrogen cycle.

[0004] Over the past few decades, researchers have studied various transition metal electrodes, including copper, iron, nickel, and cobalt, for the electrochemical reduction of NO3 in water. - Among these transition metals, low-cost, non-toxic copper-based electrocatalysts exhibit strong NO3-reduction properties. - Its adsorption capacity allows it to rapidly adsorb NO3 at a relatively low onset potential. - Converted to NO2 - However, one bottleneck of the copper electrode is in NO3RR (NO3 - (Reduction reaction) Electrochemical process of NO2 - The accumulation of NO2 - More toxic than NO3 -Larger. Reports indicate that various noble metal electrocatalysts can effectively generate atomic hydrogen (H*), which then attacks and breaks NO bonds, thus achieving NO3RR. Some studies have also found that copper oxide exhibits high activity in promoting furfural hydrogenation through the adsorption and preferential dissociation of H2 molecules. Therefore, it can be inferred that copper oxide, as an electrocatalyst, may possess similar adsorption and dissociation characteristics of H2O as noble metal electrodes (such as Pd, Pt, Rh, etc.). Studies have found that the adsorption and dissociation characteristics of H2O can generate sufficient H* (through H2O + e-). - →H* + OH - This process not only inhibits the negative effects of hydrogen generation but also provides a good foundation for achieving NO3RR. However, current research mostly focuses on the synergistic effects between metallic copper and other auxiliary metals, with few reports on the role of the synergistic effects between different valence states of copper itself in the NO3RR process. Summary of the Invention

[0005] The purpose of this invention is to provide a copper-oxidized copper composite material, which is a three-dimensional polycrystalline spherical nanocluster that can be used for the electrocatalytic reduction of nitrates in polluted water to produce ammonia.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A copper-copper oxide composite material, wherein the composite material is loaded on carbon fiber paper, and the composite material is prepared by the following steps: Step 1: Pre-treat the carbon fiber paper to remove surface oil and impurities; Step 2: Place the carbon fiber paper from Step 1 in a sodium sulfate electrolyte containing CuSO4, and deposit metallic copper on the surface of the carbon fiber paper using a chronoamperometry method. Step 3: Immerse the carbon fiber paper from Step 2 in a mixed solution of NaOH and (NH4)2S2O8, then remove it and heat it in a tube furnace. Step 4: Using the carbon fiber paper from Step 3 as the working electrode, and the platinum sheet electrode and the saturated calomel electrode as the counter electrode and reference electrode, respectively, electrolysis is performed in an alkaline electrolyte containing 0.1 M nitrate using cyclic voltammetry to obtain the copper-oxidized copper composite material.

[0007] Further, in the CuSO4-containing sodium sulfate electrolyte, the concentration of CuSO4 is 70 mM to 80 mM, and the concentration of sodium sulfate is 0.50 M. Preferably, the concentration of CuSO4 is 70 mM, and the concentration of sodium carbonate is 0.50 M.

[0008] Furthermore, the parameters for the chronoamperometry in step 2 are: rotor speed 600~1000 rpm, deposition potential 0.3 Vvs. RHE, and scan rate 200~250 mV s.-1 The deposition time was 800 s. Preferably, the rotor speed was 600 rpm, the deposition potential was 0.3 V vs. RHE, and the scan rate was 200 mV / s. -1 The deposition time was 800 s.

[0009] Further, in the mixed solution of NaOH and (NH4)2S2O8, the concentration of NaOH is 2.5~3 M, and the concentration of (NH4)2S2O8 is 0.125~0.145 M. Preferably, the concentration of NaOH is 2.5 M, and the concentration of (NH4)2S2O8 is 0.125 M.

[0010] Further, in step 3, the soaking conditions are 20-30℃ for at least 15 minutes, and the heating conditions are an inert gas atmosphere, 550℃~650℃, and 2 hours. Preferably, the soaking conditions are 20-30℃ for 15 minutes, and the heating conditions are an inert gas atmosphere, 550℃, and 2 hours.

[0011] Furthermore, in step 4, the electrolysis conditions using cyclic voltammetry are -0.5~0.5 V vs. RHE, for 50 cycles.

[0012] The application of the above-mentioned copper-oxidized copper composite material in the catalytic removal of nitrates from water.

[0013] The application of the above-mentioned copper-oxidized copper composite material in the catalytic preparation of ammonia from nitrates.

[0014] This invention designs a three-dimensional polycrystalline spherical nanocluster copper-oxidized copper composite material grown in situ on carbon fiber paper. The carbon fiber paper loaded with this material is used to electrocatalyze the reduction of nitrates. While removing nitrate pollution from water bodies, it can achieve excellent ammonia production performance, selectivity, and resistance to interference from impurities in actual water bodies. It can be used to remove nitrates in actual water bodies and synthesize ammonia efficiently.

[0015] The present invention has the following advantages: (1) A special structure copper-based electrocatalytic material grown in situ on carbon fiber paper is prepared by a three-step reaction (wet chemical oxidation method, pyrolysis reduction method and cyclic voltammetric electrolytic reduction method). The manufacturing cost is low and it is suitable for promotion. The preparation process is green, environmentally friendly and simple and fast.

[0016] (2) The in-situ growth of three-dimensional spherical nanoclusters of copper-oxidized copper materials on carbon fiber paper forms a self-supporting stable structure, which not only enhances the stability of the catalyst and the reaction contact area, but also allows for the tunability of the electrode size, providing convenience for practical applications.

[0017] (3) Under optimal conditions, CP-C exhibited a Faraday efficiency of up to 98% and a concentration of 22 mg cm⁻¹. -2 h -1 The high ammonia yield indicates excellent electrocatalytic performance for the reduction of nitrate to ammonia under alkaline conditions. This performance is very attractive for practical applications because it means that a highly efficient catalytic process can be achieved with relatively low energy consumption. Attached Figure Description

[0018] Figure 1 This is a schematic diagram illustrating the principle of constructing a copper-oxidized copper composite material according to the present invention.

[0019] Figure 2 The images show the morphological characteristics of the three materials (CP-A, CP-B, and CP-C) prepared in Example 1.

[0020] Figure 3 The images show the morphology and elemental analysis of the CP-C prepared in Example 1.

[0021] Figure 4 The images show the transmission electron microscope (TEM) image and diffraction pattern of the CP-C prepared in Example 1.

[0022] Figure 5 The X-ray diffraction patterns are of the three materials (CP-A, CP-B and CP-C) prepared in Example 1.

[0023] Figure 6 The X-ray photoelectron spectra of the three materials (CP-A, CP-B and CP-C) prepared in Example 1 are shown.

[0024] Figure 7 The three materials (CP-A, CP-B, and CP-C) prepared in Example 1 were subjected to a 1 M KOH solution (containing 0.1 M NO3). - ) and 1 M KOH (excluding 0.1 M NO3) - The LSV curve and Tafel plot in ().

[0025] Figure 8 The diagram shows the electrochemical active area (ECSA) and double-layer capacitance of the CP-C prepared in Example 1 in 1 M KOH solution.

[0026] Figure 9 The CP-C prepared in Example 1 was electrolyzed at different potentials for 1 hour to remove 0.1 M NO3. - Performance graphs and stability test graphs.

[0027] Figure 10The CP-C prepared in Example 1 was used to remove 0.1 M NO3 over a long period at the optimal potential. - The rendered image.

[0028] Figure 11 The CP-C prepared in Example 2 was used for long-term removal of nitrate (0.5 MNO3) from actual water bodies at the optimal potential. - The image shows the effect of high concentration (100 mM) coexisting ions (Cl). - SO4 2- CO3 2- The effect of electrolysis for 1 hour. Detailed Implementation

[0029] This invention provides a method for preparing a three-dimensional polycrystalline spherical nanocluster copper-oxidized copper composite material grown in situ on carbon fiber paper. Using the carbon fiber paper loaded with the composite material as the working electrode, by controlling the optimal potential of the electrode for electrocatalytic reduction of nitrate to ammonia, the residual nitrate in the water can be effectively converted and removed, and ammonia can be synthesized efficiently.

[0030] The preparation method provided by this invention includes: removing oil and oxide layers from the surface of carbon fiber paper (CP); depositing copper on the treated carbon fiber paper using a chronoamperometry method in a sodium sulfate electrolyte containing CuSO4; drying the copper-deposited carbon fiber paper (CP-A), immersing it in an alkaline solution containing NaOH and (NH4)2S2O8 (converting the copper on the carbon fiber paper to Cu(OH)2), and then pyrolyzing the treated carbon fiber paper under an inert gas atmosphere to obtain carbon fiber paper (CP-B) loaded with three-dimensional polycrystalline nanorod-shaped copper-oxide state. Finally, in an electrolyte containing nitrate, converting the three-dimensional polycrystalline nanorod-shaped copper-oxide state loaded on the carbon fiber paper into a stable three-dimensional polycrystalline spherical nanoclusters-oxide state copper using cyclic voltammetry, to obtain carbon fiber paper (CP-C) loaded with three-dimensional polycrystalline spherical nanoclusters-oxide state copper. This invention changes the chemical state of copper loaded on carbon fiber paper by utilizing in-situ wet chemical oxidation, pyrolysis reduction, and cyclic voltammetry electrolytic reduction methods.

[0031] The preferred embodiments of the present invention will now be described in detail with reference to specific examples. It should be understood that the following examples are given for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications and substitutions to the present invention without departing from its spirit and essence.

[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0033] Unless otherwise specified, all materials and reagents used in the following examples are commercially available. Example 1

[0034] I. Pretreatment of carbon fiber paper 1. Cut the carbon fiber paper into small pieces (1.0 cm × 2.0 cm), soak them in 30 mL of anhydrous ethanol for 10 minutes, and use ultrasound to remove surface oil and impurities. After soaking, rinse repeatedly with deionized water five times, then dry them in an oven at 60 ℃ for later use.

[0035] 2. Immerse the treated carbon fiber paper in a 1M hydrochloric acid solution for 10 minutes, and remove the oxide layer on the surface using ultrasound. After immersion, rinse repeatedly with deionized water five times, and dry in an oven at 60℃ for later use.

[0036] II. Preparation of In-situ Grown Copper Carbon Fiber Paper 1. Using pretreated carbon fiber paper as the working electrode, and platinum sheet electrode and saturated calomel electrode as the counter electrode and reference electrode, respectively, a three-electrode system is constructed.

[0037] 2. Add 25 mL of 0.50 M anhydrous sodium sulfate containing 70 mM CuSO4 to the electrolytic cell as the electrolyte.

[0038] 3. Copper ions in the electrolyte were converted into metallic copper and loaded onto carbon fiber paper using a chronoamperometry method. The rotor speed was maintained at 600 rpm, the deposition potential was 0.3 V vs. RHE, and the scan rate and deposition time were 200 mVs. -1 And 800 s.

[0039] 4. Rinse the carbon fiber paper obtained above twice with deionized water and dry it in an oven at 60 ℃ to obtain copper-loaded carbon fiber paper (CP-A).

[0040] III. Preparation of carbon fiber paper loaded with three-dimensional polycrystalline nanorods of copper-oxidized copper. 1. The prepared CP-A was immersed in an alkaline solution containing 2.5 M NaOH and 0.125 M (NH4)2S2O8 for 15 minutes. After immersion, it was washed with deionized water 3 to 5 times and dried to obtain carbon fiber paper (CP-Cu(OH)2) loaded with Cu(OH)2.

[0041] 2. After the above reaction is completed, CP-Cu(OH)2 is heated at 550°C for 2 hours in a tube furnace (inert gas atmosphere) to obtain carbon fiber paper (CP-B) loaded with three-dimensional polycrystalline nanorod copper-oxidized copper.

[0042] IV. Preparation of carbon fiber paper loaded with three-dimensional polycrystalline spherical nanoclusters of copper-oxidized copper 1. The prepared CP-B was used as the working electrode of the three-electrode system, and the counter electrode and reference electrode were a platinum sheet electrode and a saturated calomel electrode, respectively.

[0043] 2. In an alkaline electrolyte containing 0.1 M nitrate, cyclic voltammetry (CV) was used to electrolyze for 50 cycles at potentials of -0.5 to 0.5 V vs. RHE. CP-B was then converted into carbon fiber paper (CP-C) loaded with three-dimensional polycrystalline spherical nanoclusters of copper-oxidized copper.

[0044] 3. Wash the treated CP-C with deionized water 3-5 times at 60°C. o Dry in oven C for 2 hours, then remove and set aside.

[0045] Figure 2 Images a1, a2, b1, b2, c1, c2, d1, and d2 are scanning electron microscope (TEM) images of carbon fiber paper (CP), CP-A, CP-B, and CP-C, respectively. These images demonstrate the successful in-situ growth of copper materials on the CP substrate through a three-step reaction process (wet chemical oxidation, pyrolysis reduction, and cyclic voltammetric electrolytic reduction). During this process, the morphology of the copper material underwent a significant evolution from disordered distribution to rod-like shapes, and finally to a spherical structure. Figure 3 The microstructure and elemental composition of CP-C were revealed. Figure 3 C, D, and E in the figure reveal the uniform distribution of copper and oxygen elements in the carbon fiber. Figure 3 The image presented in the middle section shows a scanning electron microscope image of a single spherical nanocluster on CP-C. Combined with... Figure 3 Elemental spectrum analysis of g and h confirms that these spherical nanoclusters are composite materials composed of oxidized copper and elemental copper. Figure 4 The transmission electron microscope (TEM) image of CP-C shows the regular circular structure of individual spheres in the spherical nanoclusters, a morphological feature that indicates that the CP-C material has an excellent reaction contact area. Figure 4 The selected area electron diffraction (SAED) mode of b further confirmed the polymorphism of the CPC material by exhibiting multiple concentric rings composed of diffraction points. This polymorphic structure is extremely beneficial for electron transfer in the nitrate reduction ammonia production process. Furthermore, Figure 4 The high-resolution transmission electron microscopy (HRTEM) at points 1 and 2 in a shows the lattice spacing of different crystal planes, providing more intuitive evidence for the polycrystalline nature of CP-C.

[0046] Figure 5X-ray diffraction (XRD) patterns of CP-A, CP-B, and CP-C are presented. These spectra clearly show the significant enhancement of the characteristic peak intensity of copper in the target material CP-C after undergoing wet chemical oxidation, pyrolytic reduction, and cyclic voltammetric electrolytic reduction processes, as well as the appearance of copper on different crystal planes and copper in oxide state. These observations are consistent with... Figure 4 The high-resolution transmission electron microscopy (HRTEM) analysis of the two marks 1 and 2 in a is consistent, which further confirms the polymorphism and composite properties of CP-C. Figure 6 Tables a and b further analyze the chemical states of copper and oxygen in the material. Figure 6 In the X-ray photoelectron spectroscopy (XPS) of Cu a, the Cu 2p spectral region showed signals of Cu(0), Cu(I), and Cu(II) species, which further revealed that the CP-C material is a composite structure of copper and copper oxide. Figure 6 The O 1s spectrum in the middle b region shows that CP-A, after wet chemical oxidation and pyrolytic reduction treatment, formed new oxygen vacancy defect states at the interface. Electrons on these defect states are easily excited, thereby improving the electrical conductivity of the material. Through cyclic voltammetry electroreduction treatment, a stable three-dimensional polycrystalline spherical nanoclusters of copper-oxide copper material CP-C was finally formed.

[0047] Electrochemical measurements were performed in an H-type electrolytic cell separated by a Nafion 115 membrane on an electrochemical workstation (CHI 760E), where a platinum sheet electrode and a saturated calomel electrode served as the counter electrode and reference electrode, respectively. The prepared carbon fiber paper loaded with three-dimensional spherical copper-oxidized nanoclusters was used as the working electrode, with the reaction area controlled at 1 cm². 2 Add 60 mL of 100 mM NO3 to both the cathode and anode chambers. - 1 M KOH solution and NO3-free - A 1 M KOH solution was used. The performance of NO3RR was evaluated by linear sweep voltammetry (LSV) and cyclic voltammetry (CV). The LSV curve was plotted at 10 mV s⁻¹. -1 The CV curve was scanned from 0 to -1.4 V vs. RHE until it reached steady state. Then, chronoamperometry (IT) tests were performed for 1 hour at different potentials with a stirring rate of 600 rpm. NO3 was detected by UV-Vis spectrophotometry (Shimadzu UV-2600i) according to standard methods. - NO2 - and NH4 + The concentration was determined to evaluate the NO3RR performance of the electrode material.

[0048] Figure 7Figure a presents the linear sweep voltammetry (LSV) curves for CP, CP-A, and CP-C. The analysis results indicate that CP is almost inactive across the entire potential range, while CP-C exhibits a significant increase in polarization current density, especially with the addition of 100 mM NO3 to the electrolyte. - Subsequently, the current signal increased significantly, indicating that NO3- precipitated on the CP-C surface. - The electrochemical reduction reaction of NO3- was demonstrated, thus proving that CP-C catalyzes the reduction of NO3-. - Potential in this area. Figure 7 The Tafel curve shown in Figure b further confirms that CP-C exhibits a lower Tafel slope after the three-step reaction, which means that the electrochemical reaction rate of the material is significantly improved. Figure 8 Tables a, b, c, and d show the electrochemical active area (ECSA) and double-layer capacitance of CP, CP-A, and CP-C, respectively. CP-C exhibits increased ECSA and double-layer capacitance, indicating superior electron transport properties and catalytic activity. These results further confirm the excellent electrochemical performance of CP-C. In summary, the unique three-dimensional polycrystalline spherical nanocluster structure of CP-C and its composite composition of copper and copper oxide endow it with excellent performance in the nitrate reduction reaction.

[0049] Figure 9 Figure a shows the yield and Faradaic efficiency of the CP-C material in the electrocatalytic reduction of nitrate to ammonia within a potential range of -0.3 to -0.9 V vs. RHE. The ammonia production rate and Faradaic efficiency were precisely quantified using the indophenol blue colorimetric method. Ammonia production continuously increased as the applied potential increased from -0.3 V vs. RHE to -0.9 V vs. RHE. However, the Faradaic efficiency initially increased and then decreased, reaching a maximum of 98% at -0.6 V vs. RHE. The high ammonia production and Faradaic efficiency of the CP-C material indicate its excellent performance in the electrocatalytic reduction of nitrate to ammonia. Considering that various nitrogen-containing byproducts may be generated during the nitrate reduction reaction (NO3RR), ... Figure 9 The study by b involved a detailed assessment of nitrite (NO2) - The Faraday efficiency of NO2 is used to ensure the accuracy of product selectivity. At lower overpotentials, NO2... - It exhibits a relatively high Faraday efficiency (43.01% at -0.3 V vs. RHE), but as the potential increases, NO2... - The Faraday efficiency decreased. This result indicates that the polycrystalline composite copper sites in CP-C materials can effectively suppress NO2 under high overpotential. - The formation of NO3 is significantly promoted. - To NH4 +The transformation. Figure 9 The further verification of the selectivity of CPC-C materials by the middle c indicates that only materials containing NO are selected. 3- NH4 can only be produced in electrolytes. + This confirms NO3 - It is NH4 + Its only nitrogen source. Figure 9 The image in section d shows the electrochemical stability test results of the CP-C material, indicating that the CP-C material is resistant to NO3- in alkaline electrolytes. - The catalytic activity showed no decline even after 10 repeated uses. The UV-Vis absorption spectrum of the long-term operation experiment (…) Figure 10 Figure a) shows the decrease in nitrate content over time, which further illustrates the effect of CP-C materials on NO3 during electrolysis. - The effective degradation capacity of NO3 in the electrolyte. With prolonged electrolysis time, the NO3 in the electrolyte... - The concentration of NO3 on the material surface decreases. - The proportion will decrease, H2O molecules or H + The proportion will increase, thus affecting NH4. + The selectivity of the generated data. For example... Figure 10 As shown in Figure b, during long-term operation, the CP-C material can continuously and effectively catalyze NO3. - To NH4 + The transformation demonstrated the conversion of 100 mM NO3 within 8 hours. - Excellent performance with near-complete degradation. Overall, CP-C materials exhibit good electrochemical stability as NO3RR catalysts. Results show that ammonia production continuously increases with increasing applied potential. Notably, a peak Faraday efficiency of 98% is achieved at -0.6 volts for RHE, highlighting the significant potential of CP-C materials in the electroreduction of nitrate for ammonia production.

[0050] Example 2 Application in water treatment 1. The actual water sample came from the Jiangning Campus of China Pharmaceutical University. The water sample was used after impurities were removed by filtering it through a 0.25 μm filter membrane.

[0051] 2. Take a piece of carbon fiber paper loaded with the CP-C material prepared in the above examples as the working electrode in the three-electrode system, wherein the platinum sheet electrode and the saturated calomel electrode are used as the counter electrode and the reference electrode, respectively. Add 60 mL of 100 mM NO3 to the cathode chamber and the anode chamber, respectively. - 1 M KOH solution and NO3-free - 1 M KOH solution.

[0052] 3. Stir with a magnetic stirrer for 30 minutes to achieve adsorption-desorption equilibrium between the catalyst and the organic matter. Activate the working electrode using cyclic voltammetry until the CV curves coincide.

[0053] 4. Subsequently, electrolysis was performed for 1 hour using the chronoamperometry method. NO3 was then detected by UV-Vis spectrophotometry according to standard methods. - NO2 - and NH4 + The concentration was determined to evaluate the performance of the electrode material.

[0054] Figure 11 Figure 'a' shows the actual water sampling location and initial pollutant content. Before the electrolysis test, the NO3 in the water was... - Add to a higher concentration of 50 mM. Figure 11 As shown in Figure b, after 8 hours of continuous electrolysis, 50 mM NO3... - It was effectively removed in actual water bodies, resulting in a high yield of NH4. + . Figure 11 c shows the effect of coexisting ions on the NO3RR activity of CP-C, when the electrolyte contains 100 mM of common natural water anions (Cl). - SO4 2- CO3 2- Even at certain conditions, CP-C still exhibits considerable NO3RR catalytic activity, further demonstrating that CP-C can effectively catalyze NO3RR in complex aquatic environments. This characteristic makes the catalyst proposed in this invention a promising candidate for effective treatment of real-world water bodies.

Claims

1. A copper-copper oxide composite material, characterized in that, The composite material is loaded onto carbon fiber paper and prepared using the following steps: Step 1: Pre-treat the carbon fiber paper to remove surface oil and impurities; Step 2: Place the carbon fiber paper from Step 1 in a sodium sulfate electrolyte containing CuSO4, and deposit metallic copper on the surface of the carbon fiber paper using a chronoamperometry method. In the sodium sulfate electrolyte containing CuSO4, the concentration of CuSO4 is 70 mM~80 mM, and the concentration of sodium sulfate is 0.50 M. The parameters for the chronoamperometry in step 2 are: rotor speed 600~1000 rpm, deposition potential 0.3 V vs. RHE, and scan rate 200~250 mV s. -1 The deposition time was 800 s. Step 3: Immerse the carbon fiber paper from Step 2 in a mixed solution of NaOH and (NH4)2S2O8, then remove it and heat it in a tube furnace. In the mixed solution of NaOH and (NH4)2S2O8, the concentration of NaOH is 2.5~3 M and the concentration of (NH4)2S2O8 is 0.125~0.145 M. In step 3, the soaking conditions are 20-30℃ for more than 15 minutes, and the heating conditions are an inert gas atmosphere, 550℃~650℃ for 2 hours; Step 4: Using the carbon fiber paper from Step 3 as the working electrode, and the platinum sheet electrode and the saturated calomel electrode as the counter electrode and reference electrode, respectively, electrolysis is performed in an alkaline electrolyte containing 0.1 M nitrate using cyclic voltammetry to obtain the copper-oxidized copper composite material. In step 4, the electrolysis conditions using cyclic voltammetry are -0.5~0.5 V vs. RHE, for 50 cycles.

2. The application of the copper-oxidized copper composite material according to claim 1 in the catalytic removal of nitrates from water.

3. The application of the copper-oxidized copper composite material according to claim 1 in the catalytic preparation of ammonia from nitrates.

Citation Information

Patent Citations

  • Preparation method and application of three-dimensional composite electrode for removing nitrate in water through efficient electro-catalysis

    CN115010217A

  • Preparation method of carbon fiber loaded copper-nickel alloy nanoparticle nitrate ammonia conversion catalyst

    CN115449835A